Synchronized Spectrophotometric Determination of Tenofovir & Zidovudine in Tablets by Chemometric Approaches - Kumar, Bhupendra; P Singh, Neha; Singh, Shivani; Tiwari, Yogesh (International Journal of Psychosocial Rehabilitation, 2020)
Simultaneous spectrophotometric determination of Tenofovir and Zidovudine was performed by partial least squares (PLS), and principal component regression (PCR) methods do not require any prior graphical treatment of the overlapping spectra of two drugs in the mixture. The absorbance values in the UV-Vis spectra were measured for the wavelength points (from 210 to 330) in the spectral region 200–400 nm, considering the intervals of 1 nm. The calibration range was found to be 1-5 μg/ml for Tenofovir and 2-10 μg/ml for Zidovudine, with a correlation coefficient of 0.9999 (PLS) and 0.9999 (PCR) for Tenofovir and 0.9999 (PLS) and 0.9999 (PCR) for Zidovudine. The validation of the multivariate methods was realized by analyzing the synthetic mixtures of Tenofovir and Zidovudine. The numerical calculations were implemented with ‘Unscrambler 10.1 X’ software. The chemometrics analysis methods were satisfactorily applied to the simultaneous determination of tenofovir and zidovudine in the pharmaceutical formulation.